Microalgae-based Intestinal villi-targeting multistage biosystem for irritable bowel syndrome treatment - Jiahui Ye; Haimeng Sun; Qing Zhang; Jian He; Min Zhou (Nature Communications)
Abstract Irritable Bowel Syndrome (IBS) is a chronic gastrointestinal disorder associated with dysregulation of the gut-brain axis. Current treatment approaches often lack long-term efficacy and target specificity, and there are no drugs or formulations specifically targeting this disease. Owing to chronic and intermittent gastrointestinal motility disturbances, the pharmacokinetic parameters of IBS patients change significantly. In this research, we develop an oral engineered microalgae biosystem by integrating microalgae with myricetin nanoparticles to enhance the treatment of IBS. After cultivation and micro-nano transformation, the engineered microalgae can be captured by intestinal villi and remain attached. The nano-coating further enhances the adhesion to intestinal tissue and resistance to gastric acid. This biosystem aims to address the pharmacokinetic complications in IBS that are not resolvable by enteric-coated capsules. Interestingly, microalgae seem to exert their prebiotic potential, assisting myricetin in increasing short-chain fatty acids levels and further regulating IBS multi-organ symptoms through the gut-brain axis.